Evaluation of the risk factors for 'Maskne: ' Mask-use habits and facial care habits - Zeynep Altan Ferhatoğlu; Defne Özkoca (Galenos Publishing House, 2023)
Background and Design: 'Maskne' has become a problem since the beginning of the coronavirus disease-2019 pandemic and it is a common diagnosis in the everyday practice of dermatologists. This study aims to determine the risk factors of 'maskne', which is a type of mechanical acne; and to determine its impact on the quality of life. Materials and Methods: A total of 105 patients with acne complaints were included in this prospective study. The daily mask use habits and facial routines of the patients, along with their age, gender, skin type, disease severity (calculated by Global Acne Evaluation Scale), and the impact on quality of life (evaluated by the Acne-Specific Quality of Life questionnaire) were noted. Results: 'Maskne' severity was independent of the patient's age, disease duration, duration of mask use, the daily number of masks used, mask type, using two masks at once; and the mask-ventilation or facial cleansing habits. 'Maskne' risk increased with make-up frequency, whereas it decreased with the application of facial moisturizers. Quality of life decreases significantly due to 'maskne' in female patients. Conclusion: Patients may be advised to regularly apply moisturizer to their faces and avoid the use of make-up to prevent 'maskne.' In the presence of 'maskne,'' female patients may be willing to seek treatment more because their quality of life deteriorates more than that of the males.